The effect of Saccharomyces cerevisiae and Acetobacter aceti concentration on the organoleptics of date vinegar - Maulana Cahya Sandiawan; Sutrisno Adi Prayitno; Dwi Retnaningtyas Utami (PT. Gyandharma Global Media, 2026)
Vinegar is a fermentation product produced through two main stages, namely anaerobic alcohol fermentation by Saccharomyces cerevisiae and aerobic acetic acid fermentation by Acetobacter aceti. Dates (Phoenix dactylifera L.) have a high simple sugar content so they have the potential to be used as raw material for vinegar production. This study aims to evaluate the organoleptic characteristics of date vinegar based on color and aroma parameters in various combinations of Saccharomyces cerevisiae and Acetobacter aceti concentrations. The study used a factorial Completely Randomized Design (CRD) with two factors, namely the concentration of Saccharomyces cerevisiae (0.1%; 0.2%; 0.3%) and the concentration of Acetobacter aceti (5%; 10%; 15%), resulting in nine treatment combinations. Organoleptic tests were conducted using a hedonic test involving 30 untrained panelists. Data were analyzed descriptively and statistically tested using the Friedman test, followed by the Wilcoxon test if there was a significant difference (p < 0.05). The organoleptic test results showed that the panelists' preference for the color and aroma of date vinegar differed between treatments. Treatment Y3V3 (0.3% Saccharomyces cerevisiae and 15% Acetobacter aceti) obtained the highest color preference value (4.07 ± 0.81), while treatment Y1V1 (0.1% Saccharomyces cerevisiae and 5% Acetobacter aceti) obtained the highest aroma preference value (3.73 ± 0.89). The Friedman test showed significant differences in color (p = 0.000) and aroma (p = 0.018) parameters. The Wilcoxon test confirmed differences in preference levels across several treatment pairs. Thus, variations in the concentration of Saccharomyces cerevisiae and Acetobacter aceti affected the organoleptic characteristics of date vinegar, especially color and aroma, which have implications for consumer acceptance.